Analysis of Online Learning against Biology Learning Results of Students of Class XI IPA at SMAN 1 Se-Kecamatan Pangkatan - Ikmelia Rosadar Hasibuan; Hasmi Syahputra Harahap (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study has the aim of knowing the Analysis of Online Learning on the Learning Achievement Results of Class XI Science Students at SMAN 1 Se-Kecamatan Rank. This type of research uses qualitative with the method used is descriptive. The population used is 66 public high school teachers in Pangakatan District, while the total sampling sample is 66 state high school students in Pangkatan District. Data collection techniques are carried out by conducting interviews and distributing response questionnaires to students via Google from. Instruments in the form of questionnaires and questionnaires. Data analysis techniques used descriptive analysis before carrying out descriptive analysis, Results (1) Availability of technology for students in the implementation of learning 63.73% (2) Students are more active and independent Online Learning Against Biology Learning Outcomes Class XI IPA students get 53.81% (3) Understanding of the material captured in Online Learning on Biology Learning Outcomes of Class XI Science Students 43.91% (4) Motivation and Interest of Students in Online Learning Against Biology Learning Outcomes of Class 53.81 Students (5) Use of Applications in Learning Online Learning in Online Learning on Biology Learning Outcomes of Class XI Science Students 58.79%. In this case that students have an effect on online learning on learning outcomes obtained by students.